Gigantomastia Bilateral Induced Efavirenz: A Case Report - Amos Pongbulaan; Erwin Astha Triyono (Institute of Medico-legal Publications Pvt Ltd, 2021)
The prognosis of HIV-infection has improved dramatically since the introduction of Highly Active Antiretroviral Therapy (HAART). With the need for a lifelong treatment, the longterm side effect of antiretroviral agents is an emergent issue of concern. Gigantomastia is a rare condition characterized by excessive breast growth. It may occur spontaneously, during puberty or pregnancy, or while taking certain medications. HAART medications which probably associated with gigantomastia is efavirenz. A 25-yearold woman with HIV-infection who developed bilateral gigantomastia while receiving efavirenz-based HAART regimens. The diagnosis was made after other possible causes of disease-induced gigantomastia were exclude and confirmed by mammography. Surgical treatment has been considered after failure of medical treatment. Although it is rare, physicians should be aware so that a timely diagnosis can be made. In most cases, only conservative treatment is sufficient, but in severe cases surgical intervention might be required.